2011
DOI: 10.4278/ajhp.100616-quan-200
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Beliefs, Attitudes, and Experiences of Latino Smokers: Relevance for Cessation Interventions

Abstract: Purpose Determine the extent to which Latino smokers are using effective interventions for smoking cessation, with particular focus on nicotine replacement therapy (NRT). Related aims were to explore cultural, attitudinal, knowledge, and socioeconomic variables associated with treatment use. Design Cross-sectional telephone survey of two groups of Colorado adult smokers: Latinos (n = 1010) and non-Latino whites (n = 519). Setting Colorado. Methods Computer-assisted telephone survey in either Spanish or E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 44 publications
(68 reference statements)
6
26
0
Order By: Relevance
“…37 Several studies asked participants to provide ratings of both their own addiction to cigarettes, and the general addictiveness of tobacco/cigarettes. 40,49,52,53 Other aspects of smoking included: the ease/difficulty of quitting; 38,41,43,44,46 the addictiveness of tobacco compared to other drugs; 34,40,49 and the extent to which they believed addiction was a reason for their smoking. 42,45 In many cases, participants' perceptions of addiction were not the major focus of the study, however, ratings of addiction were included as a relevant variable.…”
Section: Quantitative Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…37 Several studies asked participants to provide ratings of both their own addiction to cigarettes, and the general addictiveness of tobacco/cigarettes. 40,49,52,53 Other aspects of smoking included: the ease/difficulty of quitting; 38,41,43,44,46 the addictiveness of tobacco compared to other drugs; 34,40,49 and the extent to which they believed addiction was a reason for their smoking. 42,45 In many cases, participants' perceptions of addiction were not the major focus of the study, however, ratings of addiction were included as a relevant variable.…”
Section: Quantitative Studiesmentioning
confidence: 99%
“…The included studies consistently found that the majority of smokers agreed that smoking is addictive 32,34,36,37 or that 'smokers' in general are addicted. 33,40,42,53 The single study that asked whether people who smoke are addicted to nicotine found that 89% Latino participants and 94% non-Latino Whites agreed with the statement. 53 When asked whether they personally were addicted, most adult daily smokers reported that they were.…”
Section: Quantitative Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have asked about addiction to tobacco (Carpenter et al, 2009;Hughes, 2009;Okoli, Richardson, Ratner, & Johnson, 2009), to smoking (Levinson et al, 2007;Martin, 1990), and to cigarettes (Stippekohl et al, 2012;Torchalla, Okoli, Malchy, & Johnson, 2011;Weinstein, Slovic, & Gibson, 2004). Interestingly, only one quantitative study found in the literature asked about subjective assessments of nicotine addiction (Zinser, Pampel, & Flores, 2011). Studies also differ in whether they ask participants if they are addicted to smoking, or the more general statement that smoking is addictive.…”
Section: Smokers' Understandings Of Nicotine Addictionmentioning
confidence: 99%